Gasdermin D regulates the activation of EGFR in colorectal cancer - Ying Li; Jiayao Chen; Huijun Liang; Qindan Du; Jingjie Shen; Xiaoying Wang (Journal of Translational Medicine)
Abstract Background Gasdermin D (GSDMD) is a key effector molecule that activates pyroptosis through its N terminal domain (GSDMD-NT). However, the roles of GSDMD in colorectal cancer (CRC) have not been fully explored. The role of the full-length GSDMD (GSDMD-FL) is also not clear. In this study, we observed that GSDMD modulates CRC progression through other mechanisms in addition to activating GSDMD-NT. Methods Clinical CRC samples and human-derived CRC cell lines were used in this study. GSDMD expression was evaluated by RT-qPCR, Western blot and immunohistochemical (IHC) analysis. GSDMD knockdown and overexpression stable cell lines were established by Lentiviral transduction. CCK-8 assay, flow cytometry analysis for cell cycle, Transwell assay, and cell scratch assay were performed in vitro to explore the impact of GSDMD on CRC progression. Mouse subcutaneous transplantation tumor models were constructed to assess the role of GSDMD in vivo. Intestinal epithelial cell (IEC)-specific knockout of Gsdmd mice (Gsdmd ΔIEC) was used to evaluate the effect of GSDMD on intestinal adenoma formation in AOM-DSS and Apc min/+ mouse models. RNA sequencing was performed to explore the regulatory pathways associated with the role of GSDMD in CRC cells. Co-Immunoprecipitation (CO-IP), Western blot and immunofluorescence (IF) were conducted to investigate the interactions between GSDMD and EGFR. Exogenous addition of Gefitinib was used to evaluate the effect of GSDMD on autophosphorylation of EGFR at the Tyr1068 site. Results GSDMD was highly expressed in clinical CRC tissues and human-derived CRC cell lines. GSDMD knockdown inhibited the viability, cell cycle changes, invasion ability and migration ability of CRC cell lines in vitro and vivo, whereas GSDMD overexpression had the opposite effects. Intestinal adenoma development was reduced in Gsdmd ΔIEC mice in both AOM-DSS and Apc min/+ mouse models. GSDMD-FL interacted with EGFR and promoted CRC progression by inducing autophosphorylation of EGFR at the Tyr1068 site, subsequently activating ERK1/2. Exogenous Gefitinib abrogated the tumorigenic properties of GSDMD. Conclusions GSDMD-FL promotes CRC progression by inducing EGFR autophosphorylation at the Tyr1068 site, subsequently activating the downstream ERK1/2. Inhibition of GSDMD is a potential strategy for the treatment of colorectal cancer.